Is Extradition for Copyright Infringement Possible? - Natalia Vladimirovna Slesaryuk (Сибирское юридическое обозрение, 2012)
The article reads about the possibility to use extradition for infringement of copyright concerning citizens of the Russian Federation. The reason for raising the issue was the court case against the British citizen who was extradited to the U.S. being accused of copyright infringement.